The effect of infill pattern, infill density, printing speed and temperature on the additive manufacturing process based on the FDM technology for the hook-shaped components - Nguyen Huu Tho; Tong Cong Minh; Nguyen Phat Tai (Jurnal POLIMESIN, 2020)
The additive manufacturing technology based on the principle of material addition is an important technology in product design, manufacturing, and development. In addition, the trend in the recent future of this technology will be a major step to develop in the rapid manufacturing industry. Among the rapid prototyping technologies, the most popular FDM (fused deposition modeling) technology has been widely applied in the practice. The quality of rapid prototyping technology in general as well as FDM technology in particular mainly depends on the parameters in the prototyping and operational process. In this paper, the optimum parameters of the prototyping process based on the FDM technology are identified to improve the tensile strength of 3D printing products with PLA and PLA-copper materials. The parameters are chosen in the process of doing the experiments such as infill pattern, fill density, print speed, and print temperature. Then, based on Taguchi analysis technique, the experimental planning method is employed for design and optimization, with the support of Analysis of Variance (ANOVA) to evaluate and identify the influence of parameters on the tensile strength of the printed hook-shaped product. The results highlighted that the maximum tensile force of the sample is printed with PLA-Copper material with the optimum parameters is infill density of 75%, printing speed of 65 mm/s, and temperature of 185°C.